2007
DOI: 10.1128/jvi.00196-07
|View full text |Cite
|
Sign up to set email alerts
|

Emerin Is Hyperphosphorylated and Redistributed in Herpes Simplex Virus Type 1-Infected Cells in a Manner Dependent on both UL34 and US3

Abstract: Cells infected with wild-type herpes simplex virus type 1 (HSV-1) show disruption of the organization of the nuclear lamina that underlies the nuclear envelope. This disruption is reflected in changes in the localization and phosphorylation of lamin proteins. Here, we show that HSV-1 infection causes relocalization of the LEM domain protein emerin. In cells infected with wild-type virus, emerin becomes more mobile in the nuclear membrane, and in cells infected with viruses that fail to express UL34 protein (pU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
165
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(173 citation statements)
references
References 68 publications
7
165
1
Order By: Relevance
“…PKC and pUL97. There is accumulating evidence that the involvement of both cellular and viral protein kinases (some of which possess direct lamin-phosphorylating activity) is important for the regulation of nuclear egress of other herpesviruses as well (Klupp et al, 2001;Reynolds et al, 2002;Marschall et al, 2005;Bjerke & Roller, 2006;Park & Baines, 2006;Kato et al, 2006;Leach et al, 2007). It will be crucial to determine the exact phosphorylation target sites on lamins and lamina-associated proteins of these protein kinases for a detailed understanding of the cytomegaloviral nuclear egress.…”
Section: Conclusion: Model Of a Postulated Viral-cellular Multi-protementioning
confidence: 99%
See 1 more Smart Citation
“…PKC and pUL97. There is accumulating evidence that the involvement of both cellular and viral protein kinases (some of which possess direct lamin-phosphorylating activity) is important for the regulation of nuclear egress of other herpesviruses as well (Klupp et al, 2001;Reynolds et al, 2002;Marschall et al, 2005;Bjerke & Roller, 2006;Park & Baines, 2006;Kato et al, 2006;Leach et al, 2007). It will be crucial to determine the exact phosphorylation target sites on lamins and lamina-associated proteins of these protein kinases for a detailed understanding of the cytomegaloviral nuclear egress.…”
Section: Conclusion: Model Of a Postulated Viral-cellular Multi-protementioning
confidence: 99%
“…Recruitment of PKC to the nuclear membrane occurs during infection with HCMV, murine cytomegalovirus (MCMV) and herpes simplex virus type-1 (HSV-1) (Muranyi et al, 2002;Park & Baines, 2006;Milbradt et al, 2007). A conserved group of herpesvirus-encoded lamina-associated proteins have been implicated in the recruitment of PKC, the rearrangement of nuclear lamina components and viral nuclear egress (Reynolds et al, 2004;Muranyi et al, 2002;Leach et al, 2007;Morris et al, 2007;Fuchs et al, 2002;Farina et al, 2005;Milbradt et al, 2007; Camozzi et al, 2008). This group comprises pUL50 and pUL53 in HCMV and their homologues in other herpesviruses.…”
Section: Introductionmentioning
confidence: 99%
“…Alphaherpesviruses also express a viral serine/threonine protein kinase, pUS3, that phosphorylates lamins and lamin receptor emerin, which are thought to be involved in maintaining nuclear integrity (Leach et al, 2007;Morris et al, 2007;Mou et al, 2008). In addition, both HSV-1 and PrV pUL31 and pUL34 have been shown to be phosphorylated in a pUS3-dependent manner, and all three proteins have been found to be incorporated into primary virions (Purves et al, 1991; Granzow et al, 2004;Ryckman and Roller, 2004;Kato et al, 2005;Mou et al, 2007Mou et al, , 2009.…”
Section: Primary Envelopment and Deenvelopmentmentioning
confidence: 99%
“…HSV-1 and PrV disrupt the lamina through two viral proteins, pUL31 and pUL34, which form a complex colocalized to the inner NM (Reynolds et al, 2002;Reynolds et al, 2004;Simpson-Holley et al, 2004;Simpson-Holley et al, 2005;Bjerke and Roller, 2006). Research suggested that pUL31 and pUL34 promote viral nuclear egress by several mechanisms, including (1) affecting maturation of viral replication intermediates so that capsids assemble adjacent to the nuclear envelope, making it convenient for primary egress (Simpson-Holley et al, 2004, (2) causing displacement of and conformational changes in lamins A/C and B (Reynolds et al, 2004;Simpson-Holley et al, 2004;Bjerke and Roller, 2006), and (3) mislocalizing the membrane lamin receptors, such as the lamin B receptor and emerin, which tether lamins to the inner NM (Scott and O'Hare, 2001;Leach et al, 2007;Morris et al, 2007;Mou et al, 2008). Amazingly, expression of PrV pUL31 and pUL34 in RK-13 cells resulted in formation of vesicles in the perinuclear space, indicating that they may compose the essential budding machinery (Klupp et al, 2007).…”
Section: Primary Envelopment and Deenvelopmentmentioning
confidence: 99%
See 1 more Smart Citation